Introduction to fluid mechanics and fluid machines / Som, S.K.: Tata mcGraw-Hill 532 So693e2 2nd ed - Biswas, G.
Introduction to fluid mechanics and fluid machines / Som, S.K.: Tata mcGraw-Hill 532 So693e2 2nd ed No. of Copies : 1